Universal trend of charge radii of even-even Ca-Zn nuclei - Kortelainen, Markus; Sun, Zhonghao; Hagen, Gaute; Nazarewicz, Witold; Papenbrock, Thomas; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2022)
Radii of nuclear charge distributions carry information about the strong and electromagnetic forces acting inside the atomic nucleus. Whereas the global behavior of nuclear charge radii is governed by the bulk properties of nuclear matter, their local trends are affected by quantum motion of proton and neutron nuclear constituents. The measured differential charge radii δ(rc2) between neutron numbers N=28 and N=40 exhibit a universal pattern as a function of n=N-28 that is independent of the atomic number. Here we analyze this remarkable behavior in even-even nuclei from calcium to zinc using two state-of-the-art theories based on quantified nuclear interactions: the ab initio coupled cluster theory and nuclear density functional theory. Both theories reproduce the smooth rise of differential charge radii and their weak dependence on the atomic number. By considering a large set of isotopic chains, we show that this trend can be captured by just two parameters: the slope and curvature of δ(rc2)(n). We demonstrate that these parameters show appreciable model dependence, and the statistical analysis indicates that they are not correlated with any single model property, i.e., they are impacted by both bulk nuclear properties as well as shell structure.
CRIS-Team Scopus Importer:2022-02-25